Recycled concrete blocks used as coarse aggregate in the floor of rural facilities - Matheus Viero da Costa; Sidiclei Formagini; Rodrigo Couto Santos; Rafael Zucca; Juliano Lovatto (Semina: Ciências Exatas e Tecnológicas, 2019)
Waste from construction industry has been improperly disposed in areas located between the outskirts of Brazilian cities and rural villages. Thus, such areas have become irregular deposits of construction waste that have damaged fountainheads. In order to enable sustainable development in rural areas, the subject “construction waste reuse” has been increasingly researched. In that regard, this study has verified the feasibility of using recycled concrete blocks as coarse aggregate in the floor of rural facilities. Firstly, the particle size distribution and specific mass of the material recycled were registered. Afterwards, lines of concrete were established, where R0 was the reference line, without crushed block, R25 (250 kg/m3 of crushed block), R50 (490 kg/m3 of crushed block), and R75 (721 kg/m3 of crushed block). Cement concentration was the same for all lines. Samples were observed fresh – through slump test – and hardened – through simple compression tests and trials to measure the absorption of water. In the end, R25 demonstrated to comply with the regulations and that can be used to build floors intended to livestock facilities, pedestrians, and ground floor dwelling with no structural purposes.